2021
DOI: 10.1186/s12891-021-04852-y
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and radiological outcomes in patients who underwent posterior lumbar interbody fusion: comparisons between unilateral and bilateral cage insertion

Abstract: Background Although the original technique involves inserting two cages bilaterally, there could be situations that only allow for insertion of one cage unilaterally. However, only a few studies have compared the outcomes between unilateral and bilateral cage insertion. The purpose of this study was to compare the clinical and radiological outcomes in patients who underwent posterior lumbar interbody fusion (PLIF) between unilaterally and bilaterally inserted cages. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 26 publications
1
0
0
Order By: Relevance
“…We speculate that the focal resection of anulus fibrosus and discectomy does heavily destabilize the segment, and insertion of a single PLIF does not adequately compensate for this damage, which especially manifests in AC motion. The results of our biomechanical study support the findings of Cho et al [30], who reported 7.7 times increased pseudarthrosis rates 1 year postoperatively with ul-PLIF compared to bl-PLIF. However, others have shown adequate clinical outcomes with the use of only one PLIF cage without radiographic signs of pseudarthrosis [10].…”
Section: Ul-plif Versus Bl-plifsupporting
confidence: 91%
“…We speculate that the focal resection of anulus fibrosus and discectomy does heavily destabilize the segment, and insertion of a single PLIF does not adequately compensate for this damage, which especially manifests in AC motion. The results of our biomechanical study support the findings of Cho et al [30], who reported 7.7 times increased pseudarthrosis rates 1 year postoperatively with ul-PLIF compared to bl-PLIF. However, others have shown adequate clinical outcomes with the use of only one PLIF cage without radiographic signs of pseudarthrosis [10].…”
Section: Ul-plif Versus Bl-plifsupporting
confidence: 91%